Stable isotopes in human nutrition: laboratory methods and research applications - Abrams, S. A.; Abrams, S. A.; Wong, W. W.; Wong, W. W. (Wallingford :CABI Publishing, 2003)
This book provides readers a brief glimpse into the manufacturing processes of the various stable isotopic tracers as well as a basic understanding of the principles, study designs, sample requirements, sample preparation techniques, instrumentation requirements and methods of calculation for several stable isotope methods commonly used in nutrition-related research. The book is written with the intention of generating excitement among new users and serves as a basic reference guide to experienced users. This is, therefore, appropriate for graduate-level curriculum in nutrition and for those at any level who wish to obtain an understanding of these methods.
Keywords: AA500 - Research; VV120 - Physiology of Human Nutrition; ZZ900 - Techniques and Methodology